Investigating the function of microtubule-associated protein tau (MAPT) and its genetic association with Parkinson’s using human iPSC-derived dopamine neurons - Beevers, J (2016)
Parkinson's disease (PD) primarily manifests as loss of motor control through the degeneration of nigrostriatal dopaminergic neurons. The microtubule-associated protein tau (MAPT) locus is highly genetically associated with PD, wherein the H1 haplotype confers disease risk and the H2 haplotype is protective. As this haplotype variation does not alter the amino acid sequence, disease risk may be conferred by altered gene expression, either of total MAPT or of specific isoforms, of which there are six in adult human brain. To investigate haplotype-specific control of MAPT expression in the neurons that die in PD, induced pluripotent stem cells (iPSCs) from H1/H2 heterozygous individuals were differentiated into dopaminergic neuronal cultures that expressed all six mature isoforms of MAPT after six months' maturation. A reporter construct using the human tyrosine hydroxylase locus was also generated to identify human dopaminergic neurons in mixed cultures. Haplotype-specific differences in the inclusion of exon 3 and total MAPT were observed in iPSC-derived dopaminergic neuronal cultures and a novel variant in MAPT intron 10 increased the inclusion of exon 10 by two-fold. RNA interference tools were generated to knockdown total MAPT or specific isoforms, wherein knockdown of the 4-repeat isoform of tau protein increased the velocity of axonal transport in iPSC-derived neurons. MAPT knockdown also reduced p62 levels, suggesting an impact of tau on macroautophagy, likely through altered axonal transport. These results demonstrate how variation at a disease susceptibility locus can alter gene expression, thereby impacting on neuronal function.